Russian-Japanese Relations: Long-Term Development Factors - D. V. Streltsov (Vestnik MGIMO-Universiteta)
The article analyzes long-term external and internal factors determining the course of development of Russian-Japanese relations in 2019-2020. On the one hand, the anti-Russian component in Tokyo's foreign policy is shaped by its membership in the Security Treaty with the United States and its solidarity with the sanctions policy of the Group of Seven towards Russia. On the other hand, Japan and Russia are both interested interest in political cooperation in creating multilateral dialog mechanisms of international security in East Asia, resolving the nuclear issue on the Korean Peninsula, and easing tensions around territorial disputes in the East China and South China seas. Among the economic factors, the author focuses on the significant place of Russia in the context of Japan's task of diversifying sources of external energy supplies, as well as on Russia's desire to avoid unilateral dependence on the Chinese market while reorienting the system of foreign economic relations from the West to the East. Personal diplomacy of political leaders plays a significant role in relations between Russia and Japan, and, above all, close personal relationships and frequent meetings between Prime Minister Abe and President Putin, which make it possible to partially compensate the unfavorable image of the partner country in the public opinion of both Russia and Japan. Against the background of a deadlock in the Peace Treaty talks which emerged in 2019, the search for a way out of the diplomatic impasse is on the agenda. In the author's opinion, it would be appropriate at the first stage to proceed to the conclusion of a basic agreement on the basis bilateral relations, which would be "untied" from the Peace Treaty. In addition, Russia could stop criticizing Japan for its security policy and show greater understanding of the Japanese initiative in the field of quality infrastructure. In turn, Japan could take a number of strategic decisions on cooperation with Russia and announce them in the Prime Minister's keynote speech. In addition, Tokyo could stop positioning the issue of the peace Treaty as the main issue in relations with Russia, which would allow our countries to "untie" bilateral relations from the problem of border demarcation and focus on their positive agenda.